Statistical analysis of export potential of business entities - Borotov Sharofiddin Jumakul oglu, (THE INNOVATION ECONOMY, 2026)
This article presents a statistical analysis of the export potential of business entities in the Surkhandarya region. The study is based on official statistical data from 2020 to 2024, examining export volumes, sectoral distribution, and development dynamics. The analysis reveals that the region’s exports are primarily driven by large enterprises, while the involvement of small and medium-sized businesses remains limited. The paper also identifies key constraints affecting export growth and proposes recommendations for enhancing the export capacity of local businesses.